IoT technologies in smart cities : from sensors to big data, security and trust - AI-Turjman, Fadi; Imran, Muhammad (Control, Robotics & Sensors., 2020)
The Internet of Things (IoT) is a system of connected computing devices, mechanical and digital machines, objects and/or people that are provided with unique identifiers and the ability to transfer data over a network without requiring human-to-human or human-to-computer interaction. One of the hottest areas in technology right now is, without a doubt, the smart city and sensors in the IoT era. Smart city and sensing platforms are considered one of the most significant topics in IoT. Sensors are at the heart of this concept, and their development is a key issue if such concept is to achieve its full potential. This book is dedicated for addressing the major challenges in realizing the smart city paradigm and sensing platforms in the era of cloud and IoT. Challenges vary from cost and energy efficiency to availability and service quality. To tackle such challenges, sensors have to meet certain expectations and requirements, such as size constraints, manufacturing costs and resistance to environmental factors existing at deployment locations. The aim of this book is thus to focus on both the design and implementation aspects in smart cities and sensing applications that are enabled and supported by IoT paradigms.